Pelatihan Manajemen Kepemimpinan Manajerial PT. Wahana - Yohana F. Cahya Palupi Meilani; Rinto Rain Barry (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of implementing Community Service (PKM) WUTR Employee Leadership Management Training is (1) Provide training to participants on the importance of leadership and characteristics of good leader. (2) Provide debriefing to participants building the relationship between superiors and subordinates to achieve good performance. The method of training implementing is through providing explanations in plenary and discussing real cases. Methods of presenting training through lectures, interactive discussions. There are 67 trainees including lower level managerial and middle level manajerial. Based on the results of the activity, that all participants were very enthusiastic in participating in activities and most of the participants stated that they understood better how to direct their subordinates to better performance after training in PKM activities.